2022
DOI: 10.1364/ao.452511
|View full text |Cite
|
Sign up to set email alerts
|

Super-resolution reconstruction of terahertz images based on a deep-learning network with a residual channel attention mechanism

Abstract: To date, the existing terahertz super-resolution reconstruction methods based on deep-learning networks have achieved noteworthy success. However, the terahertz image degradation process needs to fully consider the blur and noise of the high-frequency part of the image during the network training process, and cannot be replaced simply by interpolation, which has high complexity. The terahertz degradation model is systematically investigated, and effectively solves the above problems by introducing the remainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Traditional methods, including deconvolution techniques like the Lucy-Richardson algorithm and various interpolation methods, have been instrumental in initial improvements. However, these approaches often fall short in recovering high-frequency details and handling noise variations [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional methods, including deconvolution techniques like the Lucy-Richardson algorithm and various interpolation methods, have been instrumental in initial improvements. However, these approaches often fall short in recovering high-frequency details and handling noise variations [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Su et al [ 22 ] suggested a novel subspace-and-attention-guided restoration network (SARNet), which adopted attention guidance to fuse spatio-spectral features of amplitude and phase. Yang et al [ 23 ] introduced the remaining channel mechanism and the residual channel attention mechanism to restore the high-frequency information.…”
Section: Introductionmentioning
confidence: 99%
“…While utilizing only the prior information of the blurred image itself, the total variation [34] and the normalized sparsity measurement [35] blinddeconvolution methods were also used to estimate the PSF and improve the lateral resolution, but the estimation accuracy and restoration capability are limited. In recent years, thanks to the powerful end-to-end mapping and learning capabilities of convolutional neural networks, a variety of deep learning methods [36][37][38][39][40] have also been proposed to implement the THz image super-resolution and have achieved good restoration results. However, when the system parameters (operating frequency, quasi-optical device parameters) are changed, the network needs to be retrained.…”
Section: Introductionmentioning
confidence: 99%